Computational Insights into the Potential of Withaferin-A, Withanone and Caffeic Acid Phenethyl Ester for Treatment of Aberrant-EGFR Driven Lung Cancers - Vidhi Malik; Vipul Kumar; Sunil C. Kaul; Renu Wadhwa; Durai Sundar (Biomolecules, 2021)
The anticancer activities of Withaferin-A (Wi-A) and Withanone (Wi-N) from Ashwagandha and Caffeic Acid Phenethyl Ester (CAPE) from honeybee propolis have been well documented. Here, we examined the binding potential of these natural compounds to inhibit the constitutive phosphorylation of epidermal growth factor receptors (EGFRs). Exon 20 insertion mutants of EGFR, which show resistance to various FDA approved drugs and are linked to poor prognosis of lung cancer patients, were the primary focus of this study. Apart from exon 20 insertion mutants, the potential of natural compounds to serve as ATP competitive inhibitors of wildtype protein and other common mutants of EGFR, namely L858R and exon19del, were also examined. The potential of natural compounds was compared to the positive controls such as erlotinib, TAS6417 and poziotinib. Similar to known inhibitors, Wi-A and Wi-N could displace and binds at the ATP orthosteric site of exon19del, L858R and exon20, while CAPE was limited to wildtype EGFR and exon 20 insertion mutants only. Moreover, the binding free energy of the natural drugs against EGFRs was also comparable to the positive controls. This computational study suggests that Wi-A and Wi-N have potential against multiple mutated EGFRs, warranting further in vitro and in vivo experiments.